Toxic Metals through the Prism of World Warfares (Global Journal of Science Frontier Research, 2023)
The study of effects from environmental pollution by toxic substances due to warfare is not a new subject although it remains poorly explored in many criteria More and more scientific data shows that armed conflicts and military actions significantly contribute to pollution of the environment with toxic substances and heavy metals in particular Lately Ukraine has been facing that problem in acute form The aim of the study is to provide an analytical overview of the current state of environmental pollution by toxic metals and organic substances released due to the armed conflicts exercises and protracted wars in the world and to show the possible risks for the human health and for the environment Significant accumulation of metals was observed in the battle fields small arms shooting ranges artillery mortar and jetranges as well as grenade launching grounds during exercises Weaponry residue left in the fields during warfare combustion products from ballistic missiles and products of destroyed infrastructure metallurgical combines oil depots etc pose a threat due to their long-term impact on the current and descendant population Metal emissions linked to military actions can play a significant role in the health hazard of both civillian population and military personnel that live in the area affected by pollution Military action leads to soil pollution with Pb Cu and other metals that include Cd Sb Cr Ni Zn with their further leaching into groundwater resulting in the increased risk of human exposure as a consequence More than ever today Ukraine needs legislative regulations of this impact on the environment and the population of the country improvement on systems of monitoring and biomonitoring for pollution and assessment of risks for the impact of toxic substances on the environment and humans
Keywords: toxic metals; warfare; environment; hazards for humans